Forecasting Quarter-on-Quarter Changes of German GDP with Monthly Business Tendency Survey Results - Klaus Abberger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
Results from business tendency surveys are often used to construct leading indicators. The indicators are then, for example, employed to forecast GDP growth. In this article more detailed results of business tendency surveys are used to forecast quarter-onquarter GDP growth. The target series is very challenging because this type of growth rate leads to quite volatile time series. The present study focuses on German GDP data and survey results provided by the Ifo Institute. Since numerous time series of possible indicators result from the surveys, methods that can handle this setting are applied. One candidate method is principal component analysis, which is used to reduce dimensionality. On the other hand, subset selection procedures are applied. For the present setting the latter method seems more successful than principal components. But this is not a statement about the two types of procedures in general. Which method should be favoured depends very much on the aims of the specific study.
Keywords: C22; C42; E32; 330; Business tendency surveys; business cycle analysis; principal component regression; subset selection